Penerapan API (Application Programming Interface) MIDTRANS Sebagai Payment Gateway Pada Indekos Berbasis Website - Pranatawijaya, Viktor Handrianus; Yulianto, Hendra (Universitas Palangka Raya, 2022)
In the Big Indonesian Dictionary (KBBI), boarding house is staying at someone else's house with or without food (by paying monthly). The emergence of new technologies in the industrial revolution will fundamentally change the way people work and live. In the industrial era 4.0, internet technology facilitates communication between humans and humans with machines that are no longer limited by space and time. One technology that is a key aspect of competitiveness in the industrial era 4.0, namely financial technology (fintech), especially in the online payment gateway sector (payment gateway) which, if applied to the boarding house business, will be very helpful in making the rental payment process more efficient and practical. compared to conventional payments. The research methodology used in implementing the Midtrans API (Application Programming Interface) as a Payment Gateway in this website-based boarding house is the waterfall method. In this methodology, several steps are taken to build software, namely: Analysis, Design, Coding, Testing and Maintenance. Testing this website using Blackbox testing. As a result of implementing a payment gateway using the Midtrans API, now boarding house payments can be made online via bank transfer or e-wallet in real time without the need to confirm payments manually again.